2021
DOI: 10.3389/fcell.2021.666631
|View full text |Cite
|
Sign up to set email alerts
|

Force-Induced Autophagy in Periodontal Ligament Stem Cells Modulates M1 Macrophage Polarization via AKT Signaling

Abstract: Autophagy, a lysosomal degradation pathway, serves as a protective cellular mechanism in maintaining cell and tissue homeostasis under mechanical stimulation. As the mechanosensitive cells, periodontal ligament stem cells (PDLSCs) play an important role in the force-induced inflammatory bone remodeling and tooth movement process. However, whether and how autophagy in PDLSCs influences the inflammatory bone remodeling process under mechanical force stimuli is still unknown. In this study, we found that mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…Recently, our group showed that TLR3 induced the expression IFN-γ-independent IDO, resulting in inhibition of peripheral blood mononuclear cell (PBMC) proliferation and upregulation of a Treg-specific gene marker, forkhead box P3 or FOXP3 [7]. Additionally, mechanical stimuli have also been applied in vitro to regulate immunomodulatory properties of both PDL cells [35,36] and bone marrow-derived MSCs (BM-MSCs) [37] PDL cells are considered as mechanosensory cells that can perceive and respond to mechanical stress driven by mastication, speech or orthodontic movement [38]. Several studies suggested that mechanical stimuli are important factors in regulating periodontal tissue homeostasis [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group showed that TLR3 induced the expression IFN-γ-independent IDO, resulting in inhibition of peripheral blood mononuclear cell (PBMC) proliferation and upregulation of a Treg-specific gene marker, forkhead box P3 or FOXP3 [7]. Additionally, mechanical stimuli have also been applied in vitro to regulate immunomodulatory properties of both PDL cells [35,36] and bone marrow-derived MSCs (BM-MSCs) [37] PDL cells are considered as mechanosensory cells that can perceive and respond to mechanical stress driven by mastication, speech or orthodontic movement [38]. Several studies suggested that mechanical stimuli are important factors in regulating periodontal tissue homeostasis [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway has been reported to be involved in the mechanical force-induced osteoblast differentiation of PDLSCs. 41 , 42 The MAPK signaling pathway also have been found to participate in the mechano-transduction of PDLSCs. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…He et al [ 32 ] observed increased expression of pro-inflammatory cytokines in in vitro cultured macrophages after adding conditioned medium from hPDLSCs treated with mechanical forces through hydrogen sulfide (H 2 S) production. Jiang et al [ 33 ] also showed increased M1 macrophage polarization after stimulating macrophages with supernatant of hPDLSCs, which were treated with compressive forces for 12 h in vitro . Zhao et al [ 46 ] also demonstrated enhanced in vitro M1 macrophage polarization by adding exosomes secreted from hPDLSCs which were stimulated with static compressive forces for 4 h. It should be noted that these three studies [ 32 , 33 , 46 ] were conducted in the absence of any inflammatory stimuli and this might underlie the promotion of M1 polarization by mechanically treated hPDLSCs.…”
Section: Immune Cell Modulation By Hpdlscs In Different Otm Phasesmentioning
confidence: 99%
“…Jiang et al [ 33 ] also showed increased M1 macrophage polarization after stimulating macrophages with supernatant of hPDLSCs, which were treated with compressive forces for 12 h in vitro . Zhao et al [ 46 ] also demonstrated enhanced in vitro M1 macrophage polarization by adding exosomes secreted from hPDLSCs which were stimulated with static compressive forces for 4 h. It should be noted that these three studies [ 32 , 33 , 46 ] were conducted in the absence of any inflammatory stimuli and this might underlie the promotion of M1 polarization by mechanically treated hPDLSCs. Most studies imply that hPDLSCs favor M2 anti-inflammatory phenotype; however, this ability is enhanced by the inflammatory environment and in absence of any mechanical forces [ 47 50 ], whereas one study [ 47 ] revealed an enhanced polarization to the M1 pro-inflammatory phenotype in the presence of extracellular vesicles derived from lipopolysaccharide-treated hPDLSCs in the absence of mechanical forces.…”
Section: Immune Cell Modulation By Hpdlscs In Different Otm Phasesmentioning
confidence: 99%
See 1 more Smart Citation